Sunday
March 26, 2017

Post a New Question

Posted by on .

If Y' = a +bX for all i and a=the mean of Y - b*the mean of X, prove that SigmaY' = SigmaY (subscript i).
Hint: replace a with mean of Y minus b*mean of X and take the sum of both sides of the equation--that is, SigmaY'(subscript i)=Sigma(mean of Y-b*Mean of X + bX(subscript i).

I just don't even know where to begin with this problem. Please Help!!

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question